Andrographolide Ameliorates Liver Fibrosis in Mice: Involvement of TLR4/NF-κB and TGF-β1/Smad2 Signaling Pathways. (18th March 2018) - Lin, Liteng; Li, Rui; Cai, Mingyue; Huang, Jingjun; Huang, Wensou; Guo, Yongjian; Yang, Liuhong; Yang, Guizhi; Lan, Tian; Zhu, Kangshun
Abstract : Liver fibrosis is characterized by activated hepatic stellate cells (HSC) and extracellular matrix accumulation. Blocking the activation of HSC and the inflammation response are two major effective therapeutic strategies for liver fibrosis. In addition to the long history of using andrographolide (Andro) for inflammatory disorders, we aimed at elucidating the pharmacological effects and potential mechanism of Andro on liver fibrosis. In this study, liver fibrosis was induced by carbon tetrachloride (CCl4 ) and the mice were intraperitoneally injected with Andro for 6 weeks. HSC cell line (LX-2) and primary HSC were also treated with Andro in vitro. Treatment of CCl4 -induced mice with Andro decreased the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), Sirius red staining as well as the expression of α smooth muscle actin ( α -SMA) and transforming growth factor- (TGF-) β 1. Furthermore, the expression of Toll-like receptor (TLR)4 and NF- κ B p50 was also inhibited by Andro. Additionally, in vitro data confirmed that Andro treatment not only attenuated the expression of profibrotic and proinflammatory factors but also blocked the TGF- β 1/Smad2 and TLR4/NF- κ B p50 pathways. These results demonstrate that Andro prevents liver inflammation and fibrosis, which is in correlation with the inhibition of the TGF- β 1/Smad2 and TLR4/NF- κ B p50 pathways, highlighting Andro as a potential therapeutic strategy for liver fibrosis.